A Philosophical Study on Child Labour and It's Moral Issues in India: Exploring the ethical dimensions of child labour in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Human Rights and basic liberties aid us in developing our inherent abilities, intellect, talents and morality for fulfilling our substantial and psychic requirements. To completely develop as individuals, exercising and enjoying of Human Rights by every individual is essential. It is unnecessary to affirm that devoid of the acknowledgement of the right towards edification, understanding of the right for developing of each person as well as country is impossible. Childhood and Children around the globe have largely been interpreted with regards to a ‘golden age’ which is equal to virtuousness, liberty, happiness, and play and such. It is the phase during which, spreading the severities of mature life, a person barely takes on any type of accountability or commitments. Yet, at that point, it is true as well those kids are susceptible, particularly during young age. The inescapable and obstinate difficulty of child labor signifies one among the many majorly critical challenges of human rights during present era. It repudiates more than 168 million kids across the globe their essential rights to edification, playing and wellbeing. The point that kids have vulnerability, is why they require to be taken care of and sheltered from ‘the harshness of the world outside’ and throughout. Within this Study Piece, we researched the Appraisals regarding Child Labor along with its Issues of Morality within India in depth.